Hubungan Pola Asuh Orangtua Dan Self Efficacy Dengan Prestasi Â Belajar Â Mahasiswa Semester III Angkatan 2015 Di Poltekkes Majapahit MojokertoÂ - Fardiansyah, Arief; Laga Hadi Kusuma, Yudha (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractStudents academic achievement is the final assessment in college educational process. It is hypothesized that the academic achievement might he highly influenced by self-confidence and parenting styles the students are accustomed with. Confidence, in particular, bridges the influence of parenting style with the students academic achievement. Therefore, the researcher wondered how these qualities can be correlated to the academic achievement in third semester of Poltekkes Majapahit Mojokertos Class of 2015. This study is a correlational study conducted using total sampling technique. The samples were 35 students or Poltekkes Majapahit Mojokerto, gathered on May 2017. The finding revealed that half of the students received democratic parenting. It is proven by the statistic that 15 students (42.9%) with high self-efficacy receive high academic achievement, while 9 People (25.7%) receive low academic achievement. Based on Fisher Exact Probability Test, it is shown that there is a significant correlation between parenting style and student academic achievement (p value = 0.025) and there is a relationship between self-efficacy with student achievement (rs =0.364 and p value 0.032) in Pohekkes Majapahit Mojokeno s Class of 2015. 11 is concluded that the heterogeneous differences among the students academic achievement happens because there arc still parents who have not been democratic enough in caring for their children. In addition, there are still some students who have low self efficacy, shown by their uncertainty in completing a task. Thus, there is a disparity among the students achievement.Keyworsd: parenting style, self efficacy, academic achievement, student.